A STUDY OF THYROID AND SALIVARY GLANDS CHANGES IN SUICIDAL HANGING DEATHS (Journal of Forensic Medicine & Toxicology, 2021)
Background: Suicide is a major public health concern around the world. In India, hanging is one of the most common methods to commit suicide. Aim: This study aimed to observe the changes in the parotid, submandibular, and thyroid gland in suicidal hanging. Background: Suicide is a major public health concern around the world. In India, hanging is one of the most common methods to commit suicide. Aim: This study aimed to observe the changes in the parotid, submandibular, and thyroid gland in suicidal hanging.
Keywords: Focal interstitial hemorrhage; position of knot; uration of hanging; ligature mark; body weight.